Islamic Moderation as An Alternative Narrative to Extremism from The Interpretation of The Qur'an Perspective - Ghozali, Moh Alwy Amru; Indrafuddin, M Rozi (Ushuluddin, Adab, and Dakwah Faculty of State Islamic University Ponorogo, 2024)
Religious extremism is a serious problem and is hampering the realization of a Golden Indonesia in 2045. It was born because of errors in understanding religion, especially its holy books. In order to weaken its influence, countering the narrative of extremism from an interpretive perspective is urgent, and at the same time it is also necessary to strengthen Islamic moderation as an alternative narrative. Using the descriptive-analytical method, it was concluded: first, the form of narrative of extremism that is often used by hardline groups is about taghut, satan and the caliphate. Second, the counter narrative to extremism is to present a different narrative and reject extremist views about these terms from the perspective of Al-Qur'an interpretation. Third, Islamic moderation as an alternative narrative to extremism finds its source of understanding in the Koran, both regarding the nature of Islamic moderation and its forms. Keywords: Counter Narrative of Extremism; Islamic Moderation; Alternative Narrative; Interpretation of The Quran